1977
DOI: 10.1002/bit.260190505
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen transfer in mechanically agitated aqueous systems containing dispersed hydrocarbon

Abstract: SummaryThe effect of dispersed n-dodecane or n-hexadecane on the air-to-aqueous phase overall volumetric oxygen transfer coefficient in a simulated (cell-free) stirred-tank fermentor is described. The oil volume fraction ranged from zero to 0.10; the ionic strength of the aqueous phases was varied from 0 to 0.45. The air-to-aqueous phase coefficients in both oil-free (KLa) and oil-bearing (KLa*) systems were evaluated from unsteady-state experiments using a membrane-covered probe to follow the aqueous phase di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

1984
1984
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 18 publications
(4 reference statements)
3
43
0
Order By: Relevance
“…Correlations that account for the presence of an immiscible, organic liquid phase (Hassan and Robinson, 1977;Nielsen et al, 2003) or the presence of microbial cells (Cascaval et al, 2006;Galaction et al, 2004a;Galaction et al, 2005) have been previously proposed. Generally these correlations were developed for hydrocarbons as organic phases while in the present work the correlation was developed for a perfluorocarbon, perfluorodecalin, in the presence of inactive yeast cells.…”
Section: Correlations For Oxygen Mass Transfer Coefficientsmentioning
confidence: 99%
See 2 more Smart Citations
“…Correlations that account for the presence of an immiscible, organic liquid phase (Hassan and Robinson, 1977;Nielsen et al, 2003) or the presence of microbial cells (Cascaval et al, 2006;Galaction et al, 2004a;Galaction et al, 2005) have been previously proposed. Generally these correlations were developed for hydrocarbons as organic phases while in the present work the correlation was developed for a perfluorocarbon, perfluorodecalin, in the presence of inactive yeast cells.…”
Section: Correlations For Oxygen Mass Transfer Coefficientsmentioning
confidence: 99%
“…Inorganic electrolytes solutions are known to inhibit both gas bubble and oil droplet coalescence, affecting the k L a (Hassan and Robinson, 1977). The effect of using YPD medium instead of pure water in the overall k L a values was evaluated with two PFC volume fractions, 0.15 and 0.20, with the optimal geometrical conditions previously determined (1.5 dm 3 of working volume and impellers type A at Position 1), at two agitation rates (100 and 250 rpm) and at four aeration rates from 0.5 to 2.0 dm 3 Á min À1 .…”
Section: Aqueous Phasementioning
confidence: 99%
See 1 more Smart Citation
“…The addition of organic solvents to bioreactor systems has been shown to improve oxygen transfer by both enhancing the mass transfer coefficient (Hassan and Robinson, 1977), as well as the equilibrium driving force (Ho et al, 1990). The average driving force in a two-phase system is increased by adding a solvent with greater dissolved oxygen solubility than the aqueous medium.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of adding a second liquid organic phase on k L a may change, and it was shown that k L a values may increase, decrease, or remain constant, depending on the nature of the organic compound and the operating conditions [2][3][4][5][6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%